THE ISOLATION OF α-CELLULOSE & THE PREPARATION OF MICROCRYSTALLINE CELLULOSE FROM SOURSOP LEAVES (Annona muricata L.) - Yulianita Pratiwi Indah Lestari; Mi'rajunnisa; Raudatul Patimah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Powder characteristics are very important to consider in the tablet manufacturing process because they can affect the characteristics of the resulting tablets. This study aims to determine the characteristics of microcrystalline cellulose powder isolated from soursop leaves. This research method includes preparation of soursop leaves raw material, isolation of α-cellulose using 17.5% NaOH solution with 3.5% nitric acid (containing 20 mg sodium nitrite), manufacture of microcrystalline cellulose using 1 M HCl solution, and characterization of microcrystalline cellulose including quality checks. powder (organoleptic, identification, solubility), and pH testing. The results showed that the yield of microcrystalline cellulose (MCCDSr) was 96.59% against α-cellulose. The results of the characterization of microcrystalline cellulose powder including organoleptic, identification, solubility, melting point, and pH showed similar characteristics with Avicel® PH 101 as a comparison. Based on the research that has been done, the characteristics of microcrystalline cellulose powder from soursop leaves are similar to Avicel® PH 101.